IMMUNOPATHOLOGIC SYNDROMES: IMMUNE AUTOAGGRESSION DISEASES, PATHOLOGIC TOLERANCE, «TRANSPLANT AGAINST HOST» REACTIONS - P.F. Litvitsky ("Paediatrician" Publishers LLC, 2007)
This publication is the fourth and last in the series of the brief lectures devoted to the role of the system, exercising the immunobiological supervision over the individual and continuous antigenic contents of the body both in normal conditions and in the event of the pathology. It reviews the etiology, pathogenesis and main manifestations of the immune auto aggression diseases, pathologic tolerance and «transplant against host» reactions. Key words: immune auto aggression, idiotype, antigenic mimicry, tolerance, «transplant against host» reactions.